In situ measurements of fine sediment infiltration (FSI) in gravel‐bed rivers with a hydropeaking flow regime. Issue 2 (25th November 2018) - Hauer, Christoph; Holzapfel, Patrick; Tonolla, Diego; Habersack, Helmut; Zolezzi, Guido
Abstract: The overpresence of fine sediment and fine sediment infiltration (FSI) in the aquatic environment of rivers are of increasing importance due to their limiting effects on habitat quality and use. The habitats of both macroinvertebrates and fish, especially spawning sites, can be negatively affected. More recently, hydropeaking has been mentioned as a driving factor in fine sediment dynamics and FSI in gravel‐bed rivers. The primary aim of the present study was to quantify FSI in the vertical stratigraphy of alpine rivers with hydropeaking flow regimes in order to identify possible differences in FSI between the permanently wetted area (during base and peak flows) and the so‐called dewatering areas, which are only inundated during peak flows. Moreover, we assessed whether the discharge ratio between base and peak flow is able to explain the magnitude of FSI. To address these aims, freeze‐core samples were taken in eight different alpine river catchments. The results showed significant differences in the vertical stratification of FSI between the permanently wetted area during base flow and the dewatering sites. Surface clogging occurred only in the dewatering areas, with decreasing percentages of fine sediments associated with increasing core depths. In contrast, permanently wetted areas contained little or no fine sediment concentrations on the surface of the river bed. Furthermore, no statistical relationship was observed between the magnitude of hydropeaking and the sampled FSI rate. A repeated survey of FSI in the gravel matrix revealed the importance of de‐clogging caused by flooding and the importance of FSI in the aquatic environment, especially in the initial stages of riparian vegetation establishment. © 2018 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd. Abstract : The over presence of fine sediment and fine sediment infiltration (FSI) in the aquatic environment of rivers are of increasing importance due to their limiting effects on habitat quality and use.